Plant radiocarbon ages and rock surface cosmogenic 14C inventories collected at retreating ice cap margins on Baffin Island, Arctic Canada, 2013 - Gifford Miller (Arctic Data Center)
These two data sets contain the results of quantitative radiocarbon measurements in in situ tundra plants and in rock surfaces collected near dated plants, both collected close to the margins of ice caps on Baffin Island, Arctic Canada. Repository 1 provides radiocarbon measurement results for in situ plants that had been entombed beneath cold-based ice. The primary data are conventional radiocarbon ages, their calibrated ages using Northern Hemisphere IntCal13, each with one sigma uncertainties, their geographic coordinates (±10 m) and sample elevation (±20 m), both derived from hand-held GPS units. We interpret the calibrated ages to define with the plants were killed. Repository 2 contains the locations of sampled un-eroded rocks collected close to 14C-dated in situ plants, and the in situ cosmogenic 14C concentrations measured in those rock surfaces. We interpret the 14C inventories to reflect 14C production from cosmic rays when the rocks have been exposed without any ice cover, as well as 14C production at lower rates when the rocks were covered by <30 m of ice, both balanced by the decay of 14C since its production.